2010
DOI: 10.1289/ehp.1002077
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Urine Cadmium, Blood Pressure, and Hypertension: A Systematic Review and Meta-analysis

Abstract: BackgroundCadmium exposure has been inconsistently related to blood pressure.ObjectivesWe updated and reevaluated the evidence regarding the relationships of blood cadmium (BCd) and urine cadmium (UCd) with blood pressure (BP) and hypertension (HTN) in nonoccupationally exposed populations.Data sources and extractionWe searched PubMed and Web of Science for articles on BCd or UCd and BP or HTN in nonoccupationally exposed populations and extracted information from studies that provided sufficient data on popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 50 publications
5
81
0
5
Order By: Relevance
“…Kidneys are the critical target organs of cadmium toxicity. Urinary Cd excretion is a good marker of long-term Cd exposure and body burden while blood Cd may represent recent exposure (Jarup et al, 1998;Gallagher and Meliker, 2010). Collectively, our findings suggest the endothelial dysfunction in Cdexposed subjects.…”
Section: Discussionmentioning
confidence: 52%
“…Kidneys are the critical target organs of cadmium toxicity. Urinary Cd excretion is a good marker of long-term Cd exposure and body burden while blood Cd may represent recent exposure (Jarup et al, 1998;Gallagher and Meliker, 2010). Collectively, our findings suggest the endothelial dysfunction in Cdexposed subjects.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies have reported that chronic exposure to Cd increases the risk of tumors in humans [288][289][290] . However, large epidemiological studies are necessary to demonstrate whether long term Cd contamination is responsible for HCC development in humans, as in animal models.…”
Section: Cadmiummentioning
confidence: 99%
“…The higher BCF of Pb, Cu, Ni and Cd in liver compare to other organs could be attributed to the fact that the route of heavy metal entry into the experimental organism is not only via the lungs as the mouth and the skin can also serve as route of entry [1]. The high BCF recorded in this studies could be the reason why vacuolization, necrosis and nucleus condensation were noticed in the liver [51,52,53]. Higher BCF was also obtained in the lungs, kidney and heart, this higher BCF are responsible for the degenerated renal tubules, Bowman's capsule and contraction of glomeruli with reference to the kidney [49], lung and heart irritation [50,51].…”
Section: Haematological Analysis and Histopathologymentioning
confidence: 78%